Le pouvoir de l’amour - EMMA (Emma, 2020)
Salut à toutes et tous, en ces temps confinés j’ai pensé vous mettre à disposition cette histoire inédite de mon tome 3 « La charge émotionnelle ». Je souhaite plein de …
Keywords: approches et analyses; bande-dessinée; care; charge mentale; discipline; discours dominant; femmes*; hétérosexisme; identités LGBTQIA2+; pédagogie; ressource en ligne; santé; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Gouverner la vie privée: l'encadrement inégalitaire des séparations conjugales en France et au Québec - Biland, Émilie (ENS Éditions, 2019)
"L'implication de l'État dans la vie privée pose problème : les individus ont davantage de droits que par le passé, mais certains de leurs comportements, jugés problématiques pour la collectivité, justifient un interventionnisme renouvelé, dans lequel acteurs privés et mécanismes de marché occupent une place croissante. En tension entre libéralisme et normalisation, cette action publique participe aux recompositions des rapports sociaux, entre les classes sociales, entre les genres, ainsi qu'entre la population majoritaire et les personnes racisées. Objet de vifs débats et de réformes récurrentes, la régulation par le droit des séparations conjugales est un observatoire précieux de ces recompositions, ici analysées à partir de trois enquêtes collectives, qualitatives et quantitatives, menées des deux côtés de l'Atlantique. En France comme au Québec, l'accès aux procédures, les interactions avec les professionnel.les et l'encadrement des modes de vie sont les trois dimensions constitutives du gouvernement de la vie privée. Cependant, chacun des contextes n'articule pas de la même manière inégalités de classe et inégalités de genre. En scrutant la production institutionnelle des inégalités privées, cet ouvrage invite à imaginer des voies alternatives, dans la sphère privée comme dans la sphère publique, pour que la politique des droits tienne ses promesses émancipatrices."
Section: 257 pages : tableaux ; 23 cm.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; droit des femmes*; droits des femmes*; europe; famille; france; hétérosexualité; inégalités; mariage; maternité; parentalité; patriarcat; premier cycle; privilèges; périodes historiques; québec; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexualité; soc2262; soc2264; sociologie; systèmes d'oppressions; séparation; thématiques

Theorizing Family Change: A Review and Reconceptualization - Knapp, Stan J.; Wurm, Greg (Journal of Family Theory & Review, 2019)
We review how recent family scholarship theorizes recent family change as either a process of deinstitutionalization, in which family can no longer be understood in institutional terms, or a process of diversification, in which family life is expanding but not losing its institutional character. We argue that both approaches emerge out of and depend on a social institutional framework for understanding family that was developed in 20th-century sociology. Despite producing a wealth of research, both approaches have difficulty adequately conceptualizing the institutional character of family and providing ways of theorizing family change. We introduce an alternative to a social institutional framework, a Weberian institutional logics approach, which provides a different way to understand the institutional character of family life and thereby affords new interpretations and avenues for theory and research on family change in the 21st century.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; famille; maternité; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

« Gender Equality and Economic Inequality: Impact on Marriage » dans Gender and couple relationships - Coontz, Stephanie (Gender and couple relationships, 2016)
Changes in aggregate marriage rates and in the internal dynamics of individual marriages should be understood as the outcome of two powerful but very different trends in gender and class relations. One trend is the uneven but undeniably dramatic progress toward equality in personal life and cultural values, which has led to widespread repudiation of centuries-old gender hierarchies. The other trend is an equally powerful movement toward growing inequality, insecurity, and unpredictability in economic life, which has resulted in substantial losses for the most historically vulnerable and least-educated sections of the workforce. The ongoing gender revolution interacts with widening economic inequality in complex ways, increasing the benefits of marriage for individuals with higher earning power while increasing the risks of marriage for low-income individuals, especially women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; droits des femmes*; famille; inégalités; mariage; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques; états-unis

The Cyborg Embryo: Our Path to Transbiology - Franklin, S. (THEORY CULTURE AND SOCIETY, 2006)
It is useful on the occasion of the 21st anniversary of the ‘Cyborg Manifesto’ not only to reconsider its lessons in the context of what is frequently described as the re-engineering of ‘life itself’, but to look at Haraway’s earlier work on embryos. In this article I begin with Haraway’s analysis of embryology in the 1970s to suggest her cyborg embryo was already there, and has, if anything, gained relevance in today’s embryo-strewn society. I argue further, as the title suggests, that the cyborg embryo has been crucial in defining our path to what I am calling here, building on Haraway’s notion of trans from Modest_Witness, ‘transbiology’ - broadly meaning stem cell research, cloning, tissue engineering and regenerative medicine. To illustrate this argument I draw on recent ethnographic fieldwork in a new stem cell derivation facility in the UK built adjacent to an IVF surgery. Using this example, I explore the important and paradoxical role of IVF in the emergence of stem cell science, cloning and transbiology, suggesting that Haraway’s analysis remains crucial to understanding the ironic and contradictory, and unexpectedly generative, circumstances through which the IVF-stem cell interface - the door to transbiology - came into being.
Keywords: approches et analyses; biologie; care; corps; cours; discipline; discours dominant; fecondation in vitro; féminisme cyborg; justice reproductive; lit4700; maternité; premier cycle; ressource en ligne; santé; sciences; sciences humaines; sociologie; systèmes d'oppressions; thématiques